THE APPLICATION OF THINK TALK WRITE MODEL USING VISUAL MEDIA IN IMPROVING INTENSIVE READING SKILLS AT THE FOURTH GRADE STUDENTS. - Widyanti, Litfia Mia (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Think Talk Write Model Using Visual Media in Improving Intensive Reading Skills at the Fourth Grade Students. The objective of this research is to describe the steps on the application of Think Talk Write using visual media in improving intensive reading skills at the fourth grade students. Each cycle consisted of planning, action, observation, and reflection. Subjects of the research were students of the IVA class of SD Negeri 2 Kebadongan totaling 20 students The conclusion of this research is there are seven steps in the application of Think Talk Write model using visual media, namely (a) distribute students worksheet (b) read the problems in students worksheet (think), (c) group division, (d) discussion activities (talk), (e) write the results of group discussion (write), (f) present the discussion result, and (g) reflection and drawing conclusion; moreover it can improve intensive reading skills for the fourth grade students. It was proven by the increase of number of students achieving learning mastery ? 70 in the first cycle 62.50%, in the second cycle 80%, and in the third cycle 92.50%.Keywords: Think Talk Write, visual media, intensive reading skills